ANALYSIS OF TECHNOLOGY READINESS AT RURAL BANKS IN FACING THE INDUSTRIAL REVOLUTION 4.0 (CASE STUDY ON RURAL BANKS IN THE SPECIAL REGION OF YOGYAKARTA) - Laksana, Dwi Hari; Satoto, Shinta Heru (International Journal of Economics, Business and Accounting Research (IJEBAR), 2024)
This study aims to determine the readiness in adapting the use of information technology at Rural Banks to improve customer service during the covid-19 pandemic. This research is quantitative research conducted at the Rural Bank in the Special Region of Yogyakarta. Samples are categorized based on the category of assets according to the book and location. This study uses 6 factors that are used to see the readiness to use information technology, namely management support, facilitating conditions, management knowledge, business environment, infrastructure development, and regional competitiveness. The results show that on average, Rural Banks in the Special Region of Yogyakarta have good readiness in facing the industrial revolution 4.0. Good readiness was demonstrated by Rural Banks that were categorized as Book 3 assets in the City of Yogyakarta and Rural Banks that were categorized as Book 2 assets in Bantul Yogyakarta. Keywords: information technology, rural bank readiness, management support, knowledge, business environment